The Influence of Pocketbook to Improve Student Learning Outcomes and Motivation on Electron Configuration Material - Nurdiyati Abdullah; Ibnu Khaldun; Musri Musman (Postgraduate, University of Mataram, 2021)
This study aims to determine the increase in motivation and learning outcomes of students on the use of pocketbooks. This type of research is a quasi-experiment which was carried out with a nonequivalent control group design. The population in this study were students of class X SMA Negeri 3 Banda Aceh with 66 samples selected by random sampling, data obtained through test questions, and questionnaires. The learning outcome data were analyzed by using the t test. It shows that there is an effect of the pocketbook on the learning outcomes of the experimental class with the control. The N-gain of the experimental class was 63.09 with a fairly effective value category, while the control class was 46.58. Pocketbook also affects learning motivation with the N-gain of the experimental class at 41.48, while the control class is 32.01.